Water requirement and yield of fig trees under different drip irrigation management - Andrade,Irineu P. de S. (2014)
This work aimed to study the effect of drip irrigation management on growth and yield of the 'Roxo de Valinhos' fig tree (Ficus carica L.), at three years old, and to determine crop coefficients (Kc) and its water requirement (ETc) under Baixada Fluminense climate and soil conditions, state of Rio de Janeiro, Brazil. The study was carried out in the experimental area of SIPA (Sistema Integrado de Produção Agroecológica) in Seropédica, Rio de Janeiro State, from July 2011 to May 2012. The experimental area was divided in two blocks, named B1 (sandy clay loam texture) and B2 (loamy sand texture). In each block, irrigation frequencies (IF) of two (T1) and four days (T2) were evaluated, as well as the irrigation absence (T3). Irrigation management and water consumption determination were performed through the soil water balance, using the TDR technique. Plant growth was not affected by IF, differing only in the number of produced internodes. For both soil textures, the mean Kc was 0.60, with a significant difference (p<0.05) only for IF. The estimated mean yield showed no significant differences between both textural classes, ranging from 6,612 kg ha-1 (T3) to 8,554 kg ha-1 (T1). This study indicates the importance of irrigation frequency in the irrigation management of fig trees cultivated in soils with different physical characteristics.